THE EVOLUTION OF INGUSH CIVIL ACTIVISM: PROTEST, IDENTITY, AND THE FORMATION OF CIVIL SOCIETY - Mariami Bezhitashvili, (PEOPLE: International Journal of Social Sciences, 2025)
This study, part of my doctoral dissertation, concerns the evolution of civil activism, through the case of one indigenous North Caucasian people living on the periphery of the European space. Its objective is to analyze based on extensive fieldwork how collective memory and identity inform protest practices and shape the trajectory of civil society development in Ingushetia (unsovereign state, a Muslim-majority republic of Russia). The research employs qualitative methodology, combining content analysis of primary sources and documentary materials with newly collected oral histories from activists, “memory groups,” and narratives from media and official documents. Analytical categories such as protest ritual and political opportunities provide the framework for examining demonstrations in 1973, 1990, and 2018–2019. Findings indicate that Ingush protests reflect solidarity, resilience, and democratic aspirations. The trajectory of activism highlights continuity in themes of historical trauma, territorial justice, and identity, while the 2018–2019 demonstrations introduced new features: diversification of strategies, broader social participation with greater gender inclusivity, and a democratization of traditional authority structures. Simultaneously, activism is constrained by systemic state repression, which delegitimizes protest yet paradoxically strengthens collective resilience and motivates new generations to seek more institutionalized avenues for identity preservation. Research outcomes underscore the symbolic and ritual dimensions of protest, demonstrating how collective memory is mobilized under authoritarian conditions. Ingush activism thus serves as both a continuation of historical struggles and a modern search for democratic expression. Future scope includes comparative studies of civic activism in non-democratic contexts, with the Ingush case offering valuable insights into the intersections of minority rights, cultural preservation, and European democratic norms. Further exploration of alternative activism, including creative protest and knowledge mediation, may reveal new strategies for civic engagement. The research [PHDF-23-284] has been supported by the Shota Rustaveli National Science Foundation of Georgia.